5x-(3+x)=2(2x+5)

Simple and best practice solution for 5x-(3+x)=2(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(3+x)=2(2x+5) equation:


Simplifying
5x + -1(3 + x) = 2(2x + 5)
5x + (3 * -1 + x * -1) = 2(2x + 5)
5x + (-3 + -1x) = 2(2x + 5)

Reorder the terms:
-3 + 5x + -1x = 2(2x + 5)

Combine like terms: 5x + -1x = 4x
-3 + 4x = 2(2x + 5)

Reorder the terms:
-3 + 4x = 2(5 + 2x)
-3 + 4x = (5 * 2 + 2x * 2)
-3 + 4x = (10 + 4x)

Add '-4x' to each side of the equation.
-3 + 4x + -4x = 10 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 0 = 10 + 4x + -4x
-3 = 10 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 = 10 + 0
-3 = 10

Solving
-3 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 12x-7=5x+4l | | 6.42/(x-.07)=105 | | y=9sin^2x | | 21-X=34 | | x/1=12/3 | | 6(x-0.3)=-2(x+23) | | F(x)=5x^2-20x+8 | | 8(x-1)-6=5x+3(-5x) | | 2a-16=6 | | -3(-x+7)+5x=21 | | 6.42/x-.07=105 | | 3(x+5)(x+5)+26=47 | | 5x-(3x+x)=2(2x+5) | | 19-1x=14 | | 34.9+y=13 | | 5a^5+20a^3-40a-25= | | 8+2x=21 | | 3(x+2.84)=2x | | 9+(x-4)=15 | | -7/963x | | x^2+0.755x-0.177=0 | | 9y=8(y+8) | | -1.6(2y+15)=-1.3(2y-10) | | 3(y-2)/5=-2y | | 2(x+4)-4= | | 7(7c-8)=41 | | 4x-8=35 | | 3(4x-8)=0.2(35x+30) | | 3(2x-5+31)=14 | | 1/4y7 | | 5x+6=5(x-9) | | x/3-(3x-7)/5=(x-2)/6 |

Equations solver categories